A finite strain gradient theory for viscoplasticity by means of micromorphic regularization - Hamdoun, Ayoub; Mahnken, Rolf (PAMM)
Abstract Stretching of polycarbonate films leads to the formation of shear bands in the necking zone [1]. Standard viscoplastic material models render mesh size dependent results, which requires a mathematical regularization. To this end, we present a finite strain gradient theory for a viscoplastic, isotropic material model where we extend the model presented in [2] to a micromorphic model by introducing a new micromorphic variable as an additional degree of freedom with its first gradient [3, 4]. The variable here has the meaning of a micro plastic strain, and is coupled with the macro plastic by a micro penalty term, forcing the macro‐plastic strain to be close to the micro‐plastic strain for the targeted shear band regularization effect. We have implemented the model equations as a three dimensional initial boundary value problem in an in house FE‐tool, to simulate different geometries with different thickness and to compare it the experimental tests. The analysis is performed for a uniaxial tensile geometry as well as for a biaxial tensile geometry. The numerical examples show the ability of the model to regularize the shear bands and solve the problem of localization.

Biopolitik und Biopoethik: Modi der Aushandlung menschlichen Lebens in (Gegenwarts-)Literatur, Film und Serie - Hannebohm, Ronja (Biopolitik(en) in Literatur, Film und Serie: Aushandlungs- und Reflexionsräume vom 18. Jahrhundert bis heute)

Mathematikleistungen von Grundschulkindern im Zusammenhang mit dem von ihnen wahrgenommenen Feedback und ihren selbstbezogenen Kognitionen. Vortrag auf der Sektionstagung Empirische Bildungsforschung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF) und der Kommission Bildungsplanung, Bildungsorganisation und Bildungsrecht (KBBB). Thema: „Schule und Lehrkräfte. Bildung neu denken“ - Knickenberg, Margarita; Finke, Nils; Hellmich, Frank

An Evaluation of XCS on the OpenAI Gym - Mehlich, Florian

A Comparison of Algorithms for the Generation of Layouts based on Reconfigurable Slots on FPGAs - Tadakamalla, Yashwanth

Design and Realization of Optimized Intra-FPGA ROS 2 Communication - Middeke, Sorel Horst

A Hardware/Software Co-designed ORB-SLAM2 Algorithm for FPGA - Thiele, Simon

Implementation and Evaluation of a ReconROS-based Obstacle Avoidance Architecture for Autonomous Robots - Abooof, Alhussain

Multithreaded Software/Hardware Programming with ReconOS/Zephyr on a RISC-V-based System-on-Chip - Rao, Aniruddh P

Effizienzanalyse leichtgewichtiger Neuronaler Netze für FPGA-basierte Modulationsklassifikation - Simon-Mertens, Florian

Demonstrator for Dataflow-based DNN Acceleration for Vision Applications on Platform FPGAs - Oviasogie, Marvin Osaretin

Development of a Power Analysis Framework for Embedded FPGA Accelerators - Reuter, Lucas David

Verarbeitung von Sensordaten auf eingebetteten heterogenen FPGA-Systemen - Hamm, Robin

Fast Partial Reconfiguration for ReconOS64 on Xilinx MPSoC Devices - Klassen, Alexander

Ein Simulator für Schedulability-Experimente mit periodischen Tasks auf FPGAs - Tsague Dingo, Jorian

Evaluation of Classifier Migration Between Multiple XCS Populations - Brede, Mathis

Design and Realization of an Intra-FPGA ROS 2 Communication Infrastructure for the ReconROS Executor - Nowosad, Alexander

Design and Implementation of a RadioML Demonstrator based on an RFSoC Platform - AlAidroos, Salem

Bewertung der Xilinx Runtime Library zur Hardware/Software-Kommunikation - Evers, Gerrit

Reconfigurable Random Forest Implementation on FPGA - Raeisi Nafchi, Masood